Some aspects of manufacturing basic machine parts from modular unified castings - S. S. Tkachenko; A. V. Yantovsky; V. O. Emelyanov; K. V. Martynov (Литьë и металлургия)
The production of solid‑cast basic machine parts is very time‑consuming and economically unprofitable. It is proposed to decompose the case‑shaped parts into simple flat elements, unify them with the possibility of using them in the manufacture of related machines that perform various functions. The problems of integrating machine tool construction into the digital economy in the conditions of the developing “Industry 4.0” are considered. The possibilities of production automation and robotization of unified cast blanks for modular assembly of basic machine parts are shown.